ANALISIS DAMPAK PENJUALAN KREDIT TERHADAP PERKEMBANGAN USAHA MIKRO DI KOTA SERANG - Iba Gunawan; Aditya Purnama (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
This study aims to determine the effect of sales on business development when viewed from the indicator of sales turnover, number of workers, number of customers on “Pemancingan Serang Hijau”. In this study data was collected by means of observation, documentation and interviews. Almost all daily policies and problems were taken based on statistical methods and the results of data analysis and interpretation both qualitatively and quantitatively.MANOVA is a multivariate statistical analysis that is used in analyzing more than one dependent variable to find out whether the group averages differ significantly but are still rarely used. The purpose of the study is to apply MANOVA to determine business development when viewed from the sales turnover indicator of the number of workers, number of customers.From the results of the 2018 MANOVA test, using the test between the Subject Effect procedure obtained the Sig.0,723 value for sales turnover, while the Workforce obtained Sig.0,000 and for customers the Sig.0,000 value was obtained. This shows that the sales turnover variable does not affect credit sales, while the workforce and customers have a Sig value of less than 0.005, the workforce and customers influence credit sales towards business development in “Pemancingan Serang Hijau”.